Changes in Metabolite Patterns During Refrigerated Storage of Lamb's lettuce (Valerianella locusta L. Betcke) - Schmitzer, Valentina; Senica, Mateja; Slatnar, Ana; Stampar, Franci; Jakopic, Jerneja (Frontiers in Nutrition, 2021)
Lamb's lettuce is a popular winter salad, often grown in private vegetable plots, small local farms or in intensive vegetable production. It is usually marketed as a ready-to-eat produce in supermarkets. The aim of the study was to evaluate the changes in biochemical composition and degradation of bioactive compounds during consumer-relevant time of home-grown and store-bought Valerianella locusta “Vit” salad. Primary metabolites, assimilatory pigments as well as secondary metabolites were monitored during 1 week of refrigerated storage. Home-grown lamb's lettuce exhibited highest levels of total sugars, total organic acids, vitamin C, and total phenolic content as well as enhanced levels of most individual phenolic compounds and chloroplast pigments. Locally produced samples of lamb's lettuce also contained high levels of analyzed bioactive components. All samples retained most bioactive components during the entire period of refrigerated storage. The results underline the instability of vitamin C during refrigerated storage of lamb's lettuce and pinpoint this parameter as being the most affected by storage.